High Analytics Information Technologies: A Patent-Based Cooperation Network Analysis - Pigola, Angelica; Costa, Priscila Rezende Da; Carvalho, Luisa Margarida Cagica; Porto, Geciane Silveira; Paulo, Alex Fabianne De (International Journal of Business, Economics and Management, 2022)
Technologies that involve great part of firms are those based on high analytics information (HAI) technologies as an essential resource for operating different types of businesses. Through HAI patents analysis filed between 2000 and 2020 in the main patent offices in the world, this study aims to understand whether assignees have been developing HAI technologies in cooperation and emerging HAI technologies using social network analysis (SNA). Findings show that HAI patents assignees prioritize half of their developments in R&D internally, and the other half in partnership with other companies, primarily. It is also identified that cooperation relations are between organizations with the same nationality, especially those in South Korean and North American. In addition, United States is the main market of interest even the number of HAI technologies patented have been decreasing over the last five years. Despite this context, the identification of relational capabilities between assignees and the reconfiguration of resources, as a dynamic capability, is evidenced in HAI technologies development. Findings may support to identify HAI that still emerge in different industries, especially in service industry and support strategic Research & Development (R&D) decision-making processes to prioritize investments, identify new partnerships to innovate, or collaborate to develop public policies to foster new HAI technologies development.